Toughening polylactide by direct blending of cellulose nanocrystals and epoxidized soybean oil. Issue 46 (12th July 2019) - Mahmud, Sakil; Long, Yu; Abu Taher, Muhammad; Xiong, Zhu; Zhang, Ruoyu; Zhu, Jin
ABSTRACT: Polylactide (PLA) is a bio‐based polymeric material which is earth abundant in nature. It also possesses abundant strength and stiffness making it a promising material for industrial applications. However, its brittle behavior is currently limiting research work on them. As such, an eco‐friendly blending approach is developed in this study in order to fabricate a ductile and toughen PLA composites using renewable bio‐based materials as a precursor. Specifically, PLA, epoxidized soybean oil (ESO), and frangible powder form of cellulose nanocrystals (CNCs) are melt blended to prepare the ternary composite system (PLA/CNC/ESO). During the composite routing, it is found out that the ESO successfully attached to the surface of CNC which in turn results in CNC/ESO mixtures in the PLA matrix. This intrinsic combination induces cavitation which consumes the energy produced under the stretching and impacting, resulting in the turning of the PLA's brittle phenomenon. In fact, a reasonable increase in the ductility is observed. The elongation and notched impact strength of the ternary nanocomposite are found to be ∼32% and ∼4.8 kJ m −2, respectively, which are comparatively higher than that of neat PLA or PLA/CNC composites. Differential scanning calorimetry analyses show that the ESO layer on CNC affects the thermal characteristics of PLA in the ternary composite while thermogravimetric analysis shows that there is an increase in the char yield of the composite. Furthermore, scanning electron microscopy analysis shows that the synthesis approach adopted here enables a mechanistically turning of the PLA's brittle phenomenon to ductile. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48221. Abstract :